Transtornos psiquiátricos na distonia primária - Fernando Machado Vilhena Dias (2009)
The dystonia is a disorder characterized by involuntary movement of sustained muscle contractions, resulting in twisting movements and / or abnormal postures. It is the result of the concomitant contraction of muscle agonists and antagonists. Several studies showed no motor changes in patients with primary focal dystonia (FD). While these findings support the hypothesis of dysfunction of the interaction between the frontal cortex, basal ganglia and the thalamus in the primary dystonia, recent studies show conflicting results on psychiatric disorders and cognitive performance in FD. Blepharospasm (BM), a type of primary focal dystonia is a syndrome characterized by involuntary and sustained contractions of the eyelids. Patients with hemifacial spasm (EH) make up a good control group when it investigates no motor changes in patients with BM. The objectives of the study were to evaluate the frequency of psychiatric disorders in patients with primary focal dystonia. This was a cross-sectional study, in which he proceeded to interview and psychiatric examinations so in 47 consecutive patients with FD (M / F 16/31). Moreover, there was a case-control study in which the group of 22 patients with BM (M / F, 7 / 15) was compared to the control group EH, consisting of 29 patients (M / F, 7 / 22). It was used as tools of the psychiatric evaluation the Mini-International Neuropsychiatric Interwiew version plus (MINI-PLUS), Yale Brown Obsessive Compulsive Scale (YBOCS), Beck Depression Inventory (BDI), Hamilton Anxiety Scale (HAM A), Hamilton Depression Scale (HAM D), Liebowitz Social Anxiety Scale (LS) e Frontal Assesment Battery (BAF). In assessing the frequency of psychiatric disorders in FD, it was found, according to the MINI-PLUS, that 12.8% of patients had the diagnosis of abuse and alcohol dependence, 29.8% of major depressive disorder, 44.7% of social phobia, 10.6% of specific phobia and 10.6% of obsessive compulsive disorder. According to YBOCS, 80.9% show obsessive compulsive symptoms. When comparing the BM and EH groups, there was no statistical difference in age (p = 0.6), gender (p = 0.5), duration of symptoms (p = 0.9), schooling in years (p = 0.4). The psychiatric disorders assessed by the MINI-PLUS, also, did not reach statistical difference between the groups. The results obtained by the psychometric scales used did not reach statistical significance between groups. The scores of BAF significantly correlated with education (r = 0.5). The study shows that patients with FD have high frequency of psychiatric disorders. The cognitive functioning assessed by the BAF was not changed. However, the study did not confirm the hypothesis that the demonstrations would be driven not a particularity of FD, since there was no difference in results between BM and EH.